191Two approaches to teaching epidemiology online for capacity building in developing countries. (2nd September 2021) - Sengupta, Paramita; Myles, Puja; Heller, Emeritus Richard
Abstract: Background: Contributing to a mission to build Public Health capacity in developing countries, two online epidemiology courses are offered: a tutor facilitated Master's level module 'Introduction to Epidemiology', and a free self-study 'Basic Epidemiology' Open Online Course (OOC). We report differences between these two. Methods: Student demographics on enrolled students were abstracted. A follow-up online survey of former students was performed in January 2020. Results: Among 772 students on the Master's and 619 students on the OOC courses: respectively 29% and 39% were female; 36% and 38% were medical practitioners; 80% and 43% were from Africa. For 64% of OOC students this was their first time learning online; 17% completed the course. 82% of students formally enrolled on a Master's programme passed the module. The majority of survey respondents reported that the courses had helped with reading articles critically (81% Master's; 67% OOC) and improving professional practice (75% Master's; 67% OOC); though fewer felt that the courses helped them perform their own research (67% Master's; 51% OOC). The majority (87% Masters; 79% OOC) would recommend the course to others. Conclusions: Online epidemiology courses have the ability to reach a wide audience in the developing world and contribute to capacity building. While both Master's facilitated and self-study online courses were evaluated positively by students, the completion and potential impact was higher for the former. Key messages: Online courses reaching wide audiences can help build global capacity in epidemiology